Ethics Towards Beggars in Qur'an Perspective (An Analytical Study) - Dwi ramadhan, Farhan; Saifullah, Saifullah; Nur, Saleh; Jamal, Khairunnas (Program Studi Ilmu Al-Qur'an dan Tafsir, Universitas Islam Negeri Datokarama Palu, 2023)
In this life not everyone is born rich, many people are born in a life that is less well off or arguably poor. Even though they were born in a poor condition, they still try to fulfill their daily needs every day. However, many of these poor people choose to beg or beg for many reasons. if we see today more and more people who choose to be beggars rather than work and people who beg a lot we meet in big cities. Well, in this research the author will explain how we behave when we meet people who ask for it. The research uses Library Research. From this study it was found that when people beg or beg us, we must greet them with a happy face, give them what they ask for or apologize if we cannot give them what they ask for. Our ethics or morals towards beggars or beggars who come to us are very important, because basically the beggars who come to us are a test from Allah to test our wealth, whether we use our wealth to help the poor or not. In addition to explaining the ethics of beggars, this study also explains what ethics is, what beggars are, and how Islam views beggars.